PENGARUH TINGKAT KEHADIRAN SISWA KELAS XI KE PERPUSTAKAAN TERHADAP LITERASI MEMBACA DI MADRASAH ALIYAH NEGERI 1 SURAKARTA - Indah Nurhidayati; Nurul Meisarah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
The purpose of this research is to (1) determine the attendance rate of 11th-grade students at the library in MAN 1 Surakarta, (2) determine the reading literacy level of 11th-grade students at MAN 1 Surakarta, (3) determine the effect of the attendance rate of 11th-grade students at the library on reading literacy at MAN 1 Surakarta. This research uses a quantitative research type with a survey method. The data collection methods used are questionnaires and documentation. To test the hypothesis, statistics were used with simple regression analysis techniques. The population in this study consists of 473 students, and according to Arikunto, 25% of the population can be taken if it exceeds 100 people, so the sample size for this study is 118 respondents, namely 11th-grade students at MAN 1 Surakarta for the 2024/2025 academic year. The research results show that: 1) The attendance rate of 11th-grade students at MAN 1 Surakarta is categorized as "sufficient" with an average score of 17.2, which falls within the interval of 14-20. 2) Reading literacy among 11th-grade students at MAN 1 Surakarta is 70 students with a percentage of 59%.3) Based on the hypothesis test results using the product moment correlation and simple regression analysis, a value of 0.554 was obtained. While the significant value at 95% is 0.176, the calculated r is greater than the table r, thus it can be concluded that HA is accepted, which is "There is a significant influence between the attendance rate of 11th-grade students and reading literacy at MAN 1 Surakarta."